SOCIOECONOMIC FACTORS INFLUENCING RICE PRODCCTION IN NIGER STATE, NIGERIA - FARINDE, A. J.; YUSUF, O. J.; TAIMANDA, Z. K . (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This paper investigated the factors influencing rice production in Lavun Local Government Area of Niger state. The specific objectives of the study were to describe the personal and socio-economic characteristics of the farmers, identify rice production constraints, and determine factors associated with rice production. Purposive and random sampling procedures were used to select 100 respondents used for the study). Validated and structured interview schedule was used to elicit quantitative data. Frequency counts, percentage distribution, mean and standard deviation were used to summarize and describe the data collected, while correlation and regression analyses were used to make analytical deductions. Findings revealed that 92 percent of the rice farmers were male, mean age was 45 years and majority (89%) were married. The land ownership pattern showed that 68 percent obtained their farm through inheritance and about 70 percent sourced finance through personal saving, with no farmer borrowing from Nigeria Agricultural Co- operative and Rural Development Bank (NACRDB). The constraints faced by the farmers include lack of capital, problems of input procurement, lack of adequate extension services and drought problem being the major one. While the correlation analysis indicated that significant relationships exist between output of rice and all the variables considered in the analysis at p<0.0l, the regression analysis further showed that only years of formal education, farm size and use of improved/quality seeds significantly influenced the output of rice production at p?0.05. Thus, in order to boost local rice production and enhance food security, in Nigeria, prominence should be given to these three variables.